KONSEP AD-DIN MENURUT NAQUIB AL-ATTAS - Fauzan, Fauzan (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) Sekolah Tinggi Agama Islam Jamiatut Tarbiyah Lhoksukon, 2021)
According to Al-Attas, it is very important to look sharply at the important relationship between the concept of din and madīnah which comes from din. Dīn relates to an individual believer, and madīnah in the context of the collective or the ummat. This can be seen in the history of changing the name of the city of Yasthrib to madīnah. We must see that Al-Madīnah is called and named that way because that is where the true din is established for mankind. There the believers enslaved themselves under the authority and power of the Prophet's law. as dayyān. It is also there that the consciousness of being indebted to Allah takes its definite form, and the manner and rules of the 'payment' which are agreed upon begin to be clearly explained.